DIGITAL LITERACY SKILLS AS BASIC COMPETENCIES FOR STUDENTS IN HIGHER EDUCATION: THE EXPLORATION STUDY OF CYBER PSYCHOLOGY - Rachayu, Imma; Suwarni, Suwarni; Suranti, Dewi (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Cyberpsychology focuses on the impact of digital technology and the internet on behavior and interaction between individuals as creatures socially. This research explore data mapping related to the mental condition of health students in midwifery, nursing and nutrition study programs at three different higher education so as to find balanced data mapping related to students' psychological conditions regarding current advances in digital and internet technology which have an impact on aspects of addiction, existence, self-confidence, privacy, anxiety and social interactions between individuals. This research used developmental and qualitative methods. The questionnaire items were validated by experts and tested using the Dick & Carey, 2015 development model and the distribution of the questionnaire was carried out online with a total of 384 student respondents. Research showed that the health aspect of internet addiction students was 74.5%, impact on social was 61.8%, digital well-being was 80.8%, social comparison was 70, 7%, digital mental health at 68.1%, and fear of missing out at 76.2%, based on these aspects it was in the high category, while the aspect of worry about being a victim of cyberbullying was 48.6% in the low category. Health students were not yet fully equipped with soft skills in mastering technology, especially digital literacy, so they cannot detect early the negative impact of digital on their mental health as potential health workers professional.Keywords: Cyber, psychology, students, mental health, digital literacy. Abstrak: Siberpsikologi berfokus pada dampak teknologi digital dan internet terhadap perilaku dan interaksi antar individu sebagai makhluk sosial. Penelitian ini mengeksplorasi pemetaan data terkait kondisi mental mahasiswa kesehatan di program studi kebidanan, keperawatan, dan gizi di tiga perguruan tinggi yang berbeda untuk menemukan pemetaan data yang seimbang terkait kondisi psikologis mahasiswa terkait kemajuan teknologi digital dan internet terkini yang berdampak pada aspek kecanduan, eksistensi, kepercayaan diri, privasi, kecemasan, dan interaksi sosial antar individu. Penelitian ini menggunakan metode pengembangan dan kualitatif. Item kuesioner divalidasi oleh para ahli dan diuji menggunakan model pengembangan Dick & Carey, 2015, dan penyebaran kuesioner dilakukan secara daring dengan total 384 responden mahasiswa. Penelitian menunjukkan bahwa aspek kesehatan mahasiswa adiksi internet sebesar 74,5%, dampak pada sosial sebesar 61,8%, kesejahteraan digital sebesar 80,8%, perbandingan sosial sebesar 70,7%, kesehatan mental digital sebesar 68,1%, dan rasa takut ketinggalan sebesar 76,2%, berdasarkan aspek-aspek tersebut berada pada kategori tinggi, sedangkan aspek kekhawatiran menjadi korban cyberbullying sebesar 48,6% berada pada kategori rendah. Mahasiswa kesehatan belum sepenuhnya dibekali soft skills dalam penguasaan teknologi, terutama literasi digital, sehingga mereka belum dapat mendeteksi dini dampak negatif digital terhadap kesehatan mental mereka sebagai calon tenaga kesehatan profesional.Kata kunci: Cyber, psikologi, mahasiswa, kesehatan mental, literasi digital.